Clinical Profile of Influenza viral illness - A Recent Observation in Bangladesh (Journal of Dhaka National Medical College & Hospital, 2017)
Background: Influenza pandemic is the most serious illness human civilization ever faced regarding morbidity & mortality. The recent outbreak of influenza pandemic (June, 2009) worldwide lead to influenza surveillance study in different countries sponsored by WHO with a view to control any further epidemic or pandemic outbreak of the disease. As a part of nationwide influenza surveillance study we are studying the clinical profile of influenza viral illness among persons seeking care at Dhaka National Medical College Hospital.Methodology: It was a prospective study form June 2007 to March 2015 in 1527 patients who were hospitalized with cough & difficult breathing and those who seeked out-patien department care for fever with sore throat or cough were included as case in our study.Result: Between June 2007 to March 2015 we collected specimen from 1527 cases and tested for influenza virus in the microbiology laboratory of ICDDR,B Dhaka. 224 cases were positive for influenza virus (15% ), Influenza A and influenza B viral illness was 134 (60%) & 90 (40%) respectively. Fever was the most common complaint in all influenza cases; cough, runny nose and difficulty in respiration were also frequently encountered. Headache, bodyache & sore throat were also presenting feature.J. Dhaka National Med. Coll. Hos. 2017; 23 (02): 16-18